Faktor-Faktor Yang Mempengaruhi Pengunjung Di Agro Wisata Tirto Arum Baru Kabupaten Kendal Tahun 2020 (Indonesian Journal for Physical Education and Sport, 2021)
Abstract Agro Wisata Tirto Arum, Kendal Regency is very attractive for tourists to visit it, because it is quite fun and can enjoy the rides, culinary, hotels and events that have been provided by the manager. The purpose of this study is to describe the factors that influence visitors to the Tirto Arum Baru agro tourism, Kendal district.This type of research is a combination or better known as a mixed method, which is a combination of qualitative research and quantitative research. The research instruments used were observation, interviews, questionnaires, and documentation. The results of the research and discussion show that, 1) The characteristics of the environment have a uniqueness that becomes a magnet and causes people to be interested in visiting the area and influences visitors, 2) Facilities or supporting facilities is complete and supports and influences visitors, 3) Services are one of the factors that cause increased tourist visits and affect visitors, and 4) The social economy of the community is influenced by places or locations that are close to offices and affect visitors.The conclusion in this study is that the factors that affect visitors to the Agro Tourism of Tirto Arum Baru, Kendal Regency in 2020 do affect tourist visits, it's just that there are inhibiting factors, namely Covid-19 attacking the Indonesian tourism industry, especially in the Agro Wisata Tirto Arum Baru, Kendal Regency.